Tourist activity in Rio de Janeiro state - Marafon, Glaucio José (2018)
Tourism activity in Rio de Janeiro state goes on influenced by a diversity of landscapes, different topographic and climatic characteristics, and cultural differences within its territory. But any attempt to regionalize it, create typologies for it, and divide it into zones in the state faces a geographical diversity in its physical, economic, cultural and social dimensions. As to the landscapes in its visible facet, it is undeniable the multiplicity of its components, which form peculiar surroundings thanks to both the presence of diverse topographies and climatic, hydrographic, pedologic and geologic conditions. In these surroundings, different economic contexts and cultural and social relationships interact constantly with such elements. It is clear that tourism development in the state has strong links with its geographical profile; but we understand that it is necessary to recognize the tourist value of countryside areas and to promote tourism activity as way of supporting the economy of the state’s municipalities. For that, we see as also necessary to think of public policies to support it.